Does a strict glycemic control during acute coronary syndrome play a cardioprotective effect? Pathophysiology and clinical evidence. (August 2021) - Caturano, Alfredo; Galiero, Raffaele; Pafundi, Pia Clara; Cesaro, Arturo; Vetrano, Erica; Palmiero, Giuseppe; Rinaldi, Luca; Salvatore, Teresa; Marfella, Raffaele; Sardu, Celestino; Moscarella, Elisabetta; Gragnano, Felice; et al.
Abstract: A hyperglycemic state, also in non-diabetic subjects, may be associated with acute coronary syndrome (ACS). Aim of this review is to describe the pathophysiologic association between ACS and hyperglycemic state, the protective mechanisms of a tight glycaemic control in ACS on CV outcomes, and the supporting clinical evidence. Several mechanisms may be responsible of a poor CV outcome in subjects with hyperglycemia during ACS. Endothelial NAPDH oxidase-2 (NOX2) activation in response to high glucose alters the balance between Raf/MAPK-dependent vasoconstriction and PI3K/Akt-dependent vasodilation in favour of constriction. Hyperglycaemia induces an overproduction of superoxide by the mitochondrial electron transport chain through different molecular mechanisms. Moreover, hyperglycaemia increases the size of the infarct by causing myocardial cell death through apoptosis and reducing the collateral blood flow. High FFA concentrations lead to toxicity mechanisms in acutely ischemic myocardium. On the other hand, a tight glycaemic control in ACS exerts a cardioprotective action by anti-inflammatory and anti-apoptotic mechanisms, anti-oxidative stress, endothelium protection, FFA reduction, anti-glucotoxic effect, IR and cardiac fuel metabolisms improvement, heart stem cells protection and reduced activation of adrenergic system. Unfortunately, the clinical studies supporting the above pathophysiological background are few and sometimes controversial, more likely due the risk of hypoglycemia linked to the insulin therapy generally used during ACS. Intriguingly, GLP-1 RA and SGLT2i, demonstrated highly effective in the cardiovascular prevention in high-risk subjects without the risk of hypoglycemia, might keep this cardioprotective effect even in acute conditions such as ASC.